2006
DOI: 10.1111/j.1440-1827.2006.02042.x
|View full text |Cite
|
Sign up to set email alerts
|

Oncocytic non‐functioning endocrine tumor of the pancreas

Abstract: Herein is presented the case of a malignant non-functioning endocrine tumor of the pancreas with oncocytic features, and a discussion on the high incidence of malignancy in oncocytic endocrine pancreatic tumors. The patient was a 65-year-old woman who showed no paraneoplastic symptoms produced by functioning pancreatic endocrine tumors. The primary tumor was located in the body and tail of the pancreas, and had metastasized to the liver. Tumor cells were arranged in a ribbon-like or trabecular pattern and had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Oncocytic differentiation in pancreatic neoplasms is very rare. Oncocytic variants of pancreatic intraepithelial neoplasia (PanIN), solid pseudopapillary neoplasm, acinar cell carcinoma, pancreatoblastoma, neuroendocrine neoplasm, serous cystic neoplasm, pyloric‐type intraductal tubular adenoma, and intraductal tubular carcinoma have been described [2, 17, 51, ]. Interestingly, oncocytic variants of the tumors presented above are not currently separated as distinct clinicopathologic entities.…”
Section: Resultsmentioning
confidence: 99%
“…Oncocytic differentiation in pancreatic neoplasms is very rare. Oncocytic variants of pancreatic intraepithelial neoplasia (PanIN), solid pseudopapillary neoplasm, acinar cell carcinoma, pancreatoblastoma, neuroendocrine neoplasm, serous cystic neoplasm, pyloric‐type intraductal tubular adenoma, and intraductal tubular carcinoma have been described [2, 17, 51, ]. Interestingly, oncocytic variants of the tumors presented above are not currently separated as distinct clinicopathologic entities.…”
Section: Resultsmentioning
confidence: 99%
“…Although the incidence rate is rather low, human cases of oncocytic neuroendocrine tumors occur in several organs, such as the adrenal medulla, exocrine pancreas, and lungs. 17,27,31 In an extensive previous study, which analyzed a number of human oncocytic breast carcinomas, 24 there were a few cases showing neuroendocrine differentiation accompanied by chromogranin A expression. In the present study, a subpopulation of neoplastic cells consisting of minute tumors revealed finely granular immunoreactivity for chromogranin A, despite the lack of immunoreactivity for synaptophysin and NSE.…”
mentioning
confidence: 99%
“…Some studies reported that oncocytic tumors have a malignant clinical behavior. 86,87 In the setting of liver metastasis of oncocytic pancreatic NETs, immunohistochemical staining with neuroendocrine markers can help to differentiate hepatocellular carcinomas. Pleomorphic NETs contain more than 20% of tumor cells with marked nuclear pleomorphism (Figure 3, C).…”
Section: Pancreatic Netsmentioning
confidence: 99%